Mercury in newborn from Tapajós River Basin, Itaituba, State of Pará, Brazil - Santos, Elisabeth Conceição de Oliveira (2003)
Different types of mercury emission (Hg) in the Amazon environrnent have been contributing to increase the concentration of this metal into the drainage, reaching the aquatic biota, contaminating the food chain with methyl mercury (MeHg), and increasing human exposure to mercury. The presence of Hg and MeHg in residente mothers and newborns in risk area is an important tool for the evaluation of Hg exposure and intoxication of human populations. In this study, we evaluated Hg exposure levels in mothers and newborns and performed differential diagnosis with other congenital diseases. The study was realized between November 2000 and March 2002. AlI adults that participate in this study signed The Ethical Consent Term in their behalf and in behalf of their children. The data collected comprised epidemiological and clinical data; sampJes of blood, umbilical cord, placenta, and hai; (maternal) for Hg analysis; serum for German measles, cytomegalovirus, toxoplasmosis, and syphilis serological testo A total of 1510 women and the same number of newborn participated in the study. The mothers were 22 years old (range 12 to 46 years old) and worked as housewives (61.2%), rural workers (14.8%), and maidservant (10.9%). The mean Hg leveI in mothers blood was 11.53 !lg/l (0.38 -117.62 !lg/l). The mean Hg leveI in newborn blood was 16.68 !lg/l (0.35 -126.87 !lg/l). Birth clinical data showed low weight (7.3%), cyanosis (7.0%), andjaundice (1%); 12.3% ofnewborn required medical Cale. It was not found statistical difference between clinical data and Hg levels. The correlation among Hg concentration in newborn and mothers were strongly positive (r = 0.8019; p < 0.001) with a significant model oflinear regression (r = 0.5283; p < 0.001) in which the maternal Hg leveI presented positive value for predicting levels in the newborn. The Hg levels found in both mothers and newborn characterize an exposure similar to those observed in other populations from the Tapajós River basin, with mean levels above the acceptable limits and in some cases above the internationally established limit of biological tolerance. The variables maternal age and Hg amount showed good relationship with the Hg levels found in children as predictive factors of exposure. The Hg concentration in newborn emphasizes the special attention needed to the process of Hg intra-uterine accumulation, which has potential consequences for the development of children living in areas polluted by mercury.